All about Corduroy - Freeman, Don 1908-1978 (Viking Press, 1978)
Story 1:A toy bear in a department store wants a number of things, but when a little girl finally buys him he finds what he has always wanted most of all. Story 2: About a toy bear who wants a pocket for himself and searches for one when he is left behind in the laundromat.